Implementation of E-Commerce For Building Materials And Cement Products As A Strategy to Deal With The Omicron Variant Pandemic - Ricco Herdiyan Saputra; Winia Waziana; Dita Novita Sari (Journal of Intelligent Business and Technology Science (JIBTec), 2021)
Omicron is a new variant of SARS-CoV-2 which is currently a variant of concern (VOC). The development of Omicron which continues to increase has raised fears of a new wave of the Covid-19 pandemic. Mobile application-based technology encourages people to make information easier for the digital world during this pandemic. The majority of Indonesian people already use mobile-based online applications, which offer a variety of community needs. Technology is currently growing rapidly which makes it easier for almost all the needs of society to be carried out with technology. E-commerce is one of the technologies at this time that provides many of the needs of the community in buying and selling goods, one of which is selling building materials and cement. Not to forget the need for building materials and cement is a community need in building a house or repairing a house. With the development of technology, cement business actors are implementing e-commerce for building materials and cement so that businesses and community needs can continue during this pandemic and also cement needs in the community can be served quickly, people without having to buy directly from the store